Paraboloid-Based Spouted Bed Drying of Paddy: Aerodynamics, Temperature Distribution, and Moisture Degradation - Evin, Duygu (Mdpi, 2019)
Aerodynamics, temperature variations in the annulus, and the moisture reduction of paddy in a paraboloid-based spouted bed (PBSB) dryer without draft tube and with solid and porous draft tubes were investigated. Draft tube caused a rapid decrease in the peak pressure drop and minimum spouting velocity when compared with PBSB without a draft tube. Pressure drops with draft tubes were 17 to 30% of the values for the PBSB without a draft tube. Temperature distribution along the bed height in the annular region during drying of paddy was also investigated. Heat-up in the spouted bed without draft tube was more rapid. The experiments were conducted for 70, 90, and 110 degrees C inlet air temperatures. The required length of drying time to dry the paddy with an initial moisture content of 0.35 db to a moisture content below 0.15 db could be reduced by 50-60% using a temperature of 110 degrees C instead of 70 degrees C. No constant rate period was observed. Drying took place in the falling rate period. Drying time decreased in the case of porous draft tube rather than the solid one. The highest drying rates were achieved by spouted bed without draft tube. Drying rates were in the range of 0.62-0.1, 0.51-0.06, and 0.37-0.06 (db.min(-1)) for the spouted bed without draft tube, with porous, and solid draft tubes, respectively.
Keywords: spouted bed dryer; draft tube; drying kinetics; paddy